Robust output disturbance rejection control for anaerobic digestion processes. (March 2019) - Flores-Estrella, R.A.; Alcaraz-González, V.; García-Sandoval, J.P.; González-Álvarez, V.
Highlights: H ∞ control is an alternative to bioprocess regulation under output disturbances. Tuning based approach is an alternative to regulation under output unknown disturbances. Balance between robust regulation and control effort is addressed. Abstract: Anaerobic digestion (AD) is a powerful bioprocess used mainly in the treatment of highly polluted wastewaters with a valuable byproduct called biogas. However, the difficulties associated with the AD stable operation have prevented its worldwide application. The intrinsic complexity of the physicochemical and biological characteristics combined with the uncertain feedstock conditions, time lags and the lack of reliable measurements have hindered the application of a number of classical and advanced control strategies to deal with the control problem. On the other hand, robust H ∞ theory offers a solid framework to handle feedback regulation of state variables on the plant frequency response in the face of disturbances and model uncertainties. This contribution presents a robust H ∞ mixed sensitivity control design and tuning for output disturbances rejection and it is applied to an anaerobic digestion plant. This H ∞ control holds the balance between robustness in the Chemical Oxygen Demand (COD) regulation and control effort. Simulation results show the effectiveness and benefits of the proposed design and tuning method. COD can effectively be regulated under: (i) load perturbations; (ii) model uncertainties and (iii) persistent output disturbances induced by COD measurement faults. The controller is applied to anaerobic digestion process but the approach can be implemented in distinct applications for organic matter degradation and other similar bioprocess and biological systems.